Effectiveness of Mirror Therapy on Post Stroke Functional Ability: A Meta-Analysis - Galang Aji Samudera; Hanung Prasetya; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: Stroke is the third leading cause of death after heart disease and cancer. One of the impacts of stroke is it causes a decrease in the functional ability to carry out daily activities, therefore mirror therapy is carried out to restore the functional ability. The study aims to determine the effect of mirror therapy on the functional ability of post-stroke patients based on previous primary studies.Subjects and Method: It was a systematic review and meta-analysis study with PICO as follows: P= post-stroke patients, I= mirror therapy, C= conventional therapy, and O= functional ability. Data collection was conducted from databases, namely: Google Scholar and PubMed. The inclusion criteria used were full-text articles in English, with randomized control trial design, published in 2006-2021. The keywords used were